2018
DOI: 10.1159/000493793
|View full text |Cite
|
Sign up to set email alerts
|

High Serum CA19-9 Concentration Predicts Poor Prognosis in Elderly Patients with Stage IV Colorectal Cancer

Abstract: Background/Aim: The optimal treatment strategy for elderly patients with stage IV colorectal cancer (CRC) remains controversial due to limited research data. The purpose of this study was to evaluate treatment results and to clarify the prognostic factors, especially poor prognosis factors, in elderly patients with stage IV CRC. Methods: We retrospectively reviewed the data of 82 elderly patients (aged ≥75 years) with stage IV CRC who underwent surgical treatment at our hospital between April 2001 and March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…CA19-9 is a biomarker most often used in pancreatic ductal adenocarcinoma (PDAC) diagnosis and monitoring [7], but not routinely used or recommended in CRC diagnosis, monitoring, or prognostics. Yet, elevated CA19-9 levels are found in CRC patients with a poor prognosis compared with patients with low CA19-9 levels [14]. We found CA19-9 served as a significant but not independent prognostic tumor marker in CRC, whereas it was previously considered to hold predictive value [8,15].…”
Section: Discussionmentioning
confidence: 60%
“…CA19-9 is a biomarker most often used in pancreatic ductal adenocarcinoma (PDAC) diagnosis and monitoring [7], but not routinely used or recommended in CRC diagnosis, monitoring, or prognostics. Yet, elevated CA19-9 levels are found in CRC patients with a poor prognosis compared with patients with low CA19-9 levels [14]. We found CA19-9 served as a significant but not independent prognostic tumor marker in CRC, whereas it was previously considered to hold predictive value [8,15].…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies suggested that the prognosis of patients with cancer is significantly influenced by metastasis (42,43). EMT is known to regulate metastasis and acts as a factor in determining the prognosis of cancer patient (4446).…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate antigen 19 − 9 (CA19-9), a modi ed Lewis blood group antigen associated with speci c malignancies, increases in patients with gastrointestinal cancers (30). CA19-9 was utilized as sensitive biomarker to evaluate the adenocarcinomas of the colon and rectum, and advance stage colorectal cancer with metastasis (25,(31)(32)(33). However, the correlation between the local expression level of CA19-9 and colorectal terminal tumor sites (sigmoid and rectum) is still unclear.…”
Section: Discussionmentioning
confidence: 99%